Endovascular Treatment of Middle Cerebral Artery Aneurysms for 120 Nonselected Patients: A Prospective Cohort Study - Gory, B.; Rouchaud, A.; Saleme, S.; Dalmay, F.; Riva, R.; Caire, F.; Mounayer, C. (American Journal of Neuroradiology, 2014)
BACKGROUND AND PURPOSE: Multiple technologies have developed the endovascular approach to MCA aneurysms. We assess the safety and the efficacy of a systematic endovascular approach in nonselected patients with MCA aneurysms and determine predictors of treatment outcomes. MATERIALS AND METHODS: We analyzed data collected between January 2007 and January 2012 in a prospective clinical registry. All patients with MCA aneurysms treated by means of the endovascular approach were included. A multivariate analysis was conducted to identify predictors of complications, recanalization, and outcome. RESULTS: A total of 120 patients with 131 MCA aneurysms were included. Seventy-nine patients (65.8%) were treated electively and 41 (34.2%) in the setting of subarachnoid hemorrhage. Thirty-three of 131 aneurysms (25.2%) were treated with simple coiling, 79 aneurysms (60.3%) with balloon-assisted coiling, and 19 aneurysms (14.5%) with stent-assisted coiling. Complications occurred in 13.7% of patients. Stent-assisted coiling was significantly associated with more complications (P = .002; OR: 4.86; 95% CI, 1.60–14.72). At 1 month after treatment, both the permanent morbidity (mRS ≤2) and mortality rates were 3.3%, without any significant difference according to the endovascular techniques. Mean angiographic follow-up was 16.3 months. The rate of recanalization was 15.6% without a statistical difference, according to the technique. Larger aneurysms were a predictor of recanalization (P = .016; OR: 1.183; 95% CI, 1.02–1.36). Retreatment was performed in 10 of 131 aneurysms (7.6%). CONCLUSIONS: Even though stent-assisted coiling significantly increases the risk of procedural complications, endovascular treatment of MCA aneurysms is safe, effective, and provides durable aneurysm closure in nonselected patients. EVTendovascular treatmentHHHunt and Hess